EIA in Strengthening Law Enforcement and Penalties: A Case of Corruption in Natural Resource Sector - Sasongko, Mochamad Agung; Mizuno, Kosuke; Utomo, Suyud Warno; Koestoer, Raldi Hendro (Hasanuddin Law Review, 2024)
Corruption in Indonesia's natural resource sector is a significant issue with far-reaching consequences for environmental sustainability. Despite the detrimental effects of corrupt practices on the environment, law enforcement penalties for corruption often fail to compensate for their environmental impact. The aim of the study is to explore how the use of Environmental Impact Assessments (EIAs) strengthens law enforcement efforts and increase penalties for corrupt practices in Indonesia's natural resource sector. The method used is to collect and analyze regulations, policies, and corruption study cases to examine the relationship between EIA and corruption penalties. The results showed that EIA can help corruption cases investigation and corruption cases involving EIA receive heavier penalties. This study concluded that the Indonesian government needs to reformulate its law enforcement approach by incorporating EIA into corruption investigations and using more severe penalties to deter corruption in the natural resource sector.